2018
DOI: 10.1111/jam.13689
|View full text |Cite
|
Sign up to set email alerts
|

Impact of storm runoff onSalmonellaandEscherichia coliprevalence in irrigation ponds of fresh produce farms in southern Georgia

Abstract: Aims: To examine Salmonella and Escherichia coli in storm runoff and irrigation ponds used by fresh produce growers, and compare Salmonella serovars with those found in cases of human salmonellosis. Methods and Results: We collected water before and after rain events at two irrigation ponds on farms in southern Georgia, USA, and collected storm runoff/storm flow within the contributing watershed of each pond. Salmonella and E. coli concentrations were higher in ponds after rain events by an average of 0.46 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 39 publications
(49 reference statements)
6
25
2
Order By: Relevance
“…This analysis is in agreement with previous studies which have shown poor correlation between the ability of physicochemical factors to influence levels of S. enterica in river waters in Florida [26]. Other authors have shown that Salmonella levels in ponds are not correlated to total suspended solids (TSS) before or after rainfall events [27]. Prevalence rates of Salmonella (50%) and L. monocytogenes (31%) in the current study are greater than those reported for STEC (2.35%) using several of the same sampling dates and sites [19].…”
Section: Plos Onesupporting
confidence: 92%
“…This analysis is in agreement with previous studies which have shown poor correlation between the ability of physicochemical factors to influence levels of S. enterica in river waters in Florida [26]. Other authors have shown that Salmonella levels in ponds are not correlated to total suspended solids (TSS) before or after rainfall events [27]. Prevalence rates of Salmonella (50%) and L. monocytogenes (31%) in the current study are greater than those reported for STEC (2.35%) using several of the same sampling dates and sites [19].…”
Section: Plos Onesupporting
confidence: 92%
“…(excluding monocytogenes), and L. monocytogenes detection. Overall, these findings are not unexpected since past studies have found associations between "hydrological" factors and pathogen isolation (e.g., Goyal et al, 1977;Baudart et al, 2000;Kistemann et al, 2002;Cooley et al, 2007;Haley et al, 2009;Wilkes et al, 2009Wilkes et al, , 2011Walters et al, 2011;Luo et al, 2015;Harris et al, 2018). A study that examined associations between environmental factors and pathogen isolation from Ontario river water only detected Salmonella when surface water discharge rates were elevated, which led the authors to conclude that events that promote off-farm and in-stream transfer of microbes (e.g., rain events) must occur for detection of Salmonella in the sampled rivers (Wilkes et al, 2011).…”
Section: Salmonella Isolation and Eaea-stx Codetection Were Associatesupporting
confidence: 62%
“…In a study conducted in southeast Georgia, the presence of E. coli O157:H7 was positively correlated with the concentration of fecal coliforms, but not generic E. coli, suggesting that a single indicator may not be adequate to assess the microbiological quality of irrigation water [50]. In addition, previous studies have demonstrated that generic E. coli does not correlate well with Salmonella [49,[51][52][53], Campylobacter spp. [54], and E. coli O157:H7 [53,55] presence.…”
Section: Microbial Indicators Of Irrigation Water Contaminationmentioning
confidence: 94%
“…In another study conducted in the same area, water samples were collected from irrigation ponds (near the intake source), storm runoff from forest, and storm flow from ditches and streams to determine the incidence of Salmonella and E. coli contamination in irrigation ponds on fresh produce farms before and after twelve rain events. Results demonstrated that Salmonella and generic E. coli levels were significantly higher after rainfall events in water samples from the ponds and lower in storm runoff from forests [51]. Also, Salmonella was isolated from 100% of samples collected from storm flow in streams and ditches, suggesting that recharging streams were the possible source of Salmonella in the irrigation ponds after precipitation instead of runoff from forests [51].…”
Section: Rainfall Geographical Location and Bacterial Source Trackingmentioning
confidence: 97%
See 1 more Smart Citation